Infrastruktur Dan Kebijakan Fiskal Di Indonesia - Yanuar (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2012)
This article aims at analyzing (1) the condition of Indonesia's infrastructure compared to ASEAN countries: Philippines, Vietnam, And Thailand which have the same GDP per capita as Indonesia thas are Lower middle-income countries, (2)the financial sources(expenditures and revenues) which are used to develop and to improve quality of infrastructure from GDP an APBN (National Revenues and Expenditures Budget). Data used in the study were derived from a variety of sources: Finance Department of RI, Word Bank, Asian Development Bank, and others. The data were analyzed by using descriptive method. The result revealed that the Indonesia infrastructures are left behind compared to three ASEAN countries (Philippines, Vietnam, and Thailand). To improve the quality of Indonesia's infrastructure, two ways should be done: a)reducing(or taking off) the subsidiary of duel oil for private cars, b)increasing tax ratio because it is lower than the tax ratio in the three ASEAN countries)